Objectives, Monetary Standards, and Potentialities - Johnson, Harry G. (The Review of Economics and Statistics, 1963)
tives of policy. The main staff papers relevant to that chapter are those by Chandler [i], Klein [a], and the Scitovskys [6]. The same chapter deals in a general way with potentiali-ties — the extent to which the goals are likely to be achieved in future. A full assessment of the potentialities, however, requires evaluation of the effectiveness of the instruments of policy and the efficiency with which they can be or are likely to be used, and raises in particular the questions concerning recognition, adminis-tration, and operation lags to which this morn-ing's panel was devoted. The report does not face these issues squarely: Chapter 9, on "The Choice and Combination of Policy Instru-